Why did people refuse vaccination during the pandemic? Exploring the impacts of trust and vaccine risk perception on COVID-19 vaccine hesitancy in China - Huang, Dan; Wu, Yi; Li, Hui (Frontiers in Public Health, 2025)
BackgroundVaccination was a critical step in combating the COVID-19 outbreak, but vaccine hesitancy was a prominent global concern in the pandemic. In China, the behavior of vaccination might be affected by the past vaccine-related scandals.ObjectiveThis study investigated the factors contributing to vaccine hesitancy in China, with a focus on trust, vaccine risk perception, and self-efficacy. It aims to explore the predictors and mechanisms that influence vaccine hesitancy in China during the pandemic.MethodThe study utilized a national survey fielded in 2021, with a representative sample of 3,000 Chinese adults. Quota sampling was employed to ensure regional and demographic representation of the sample. Key variables including institutional, media, and scientific trust, vaccine risk perception, and self-efficacy were measured adopting established scales from previous studies. A mediated moderation model was proposed. Trusts were hypothesized to affect vaccine hesitancy through vaccine risk perception. Moderation effect of self-efficacy on the relationship between vaccine risk perception and vaccine hesitancy was also proposed. Mediated moderation regressions were performed for model estimation.ResultsOur analyses show that institutional trust was negatively associated with vaccine hesitancy [b = −0.41, p < 0.001, 95% CI (−0.47, −0.35)], while scientific trust and media trust was positively associated with vaccine hesitancy [b = 0.36, p < 0.001, 95% CI (0.32, 0.40); b = 0.21, p < 0.001, 95% CI (0.15, 0.27)]. Vaccine risk perception was also positively associated with vaccine hesitancy [b = 0.72, p < 0.001, 95% CI (0.68, 0.76)], with self-efficacy moderating the relationship. The relationship was more profound among those who had higher self efficacy [b = 0.29, p < 0.001, 95% CI (0.21, 0.37)]. Additionally, the mediating effects of vaccine risk perception were found.ConclusionThe findings revealed that trust in institutions significantly reduced vaccine hesitancy by lowering perceived risks. In contrast, media and scientific trust heightened vaccine risk perception and hesitancy. Additionally, the study demonstrated the role of self-efficacy in moderating these effects.